IFPRI Annual Report 2009 - International Food Policy Research Institute (International Food Policy Research Institute, 2010)
Recent years have been difficult for the world's poor and hungry. By 2009, the worst of the dramatic food price increases had passed, but the world was still reeling from the global economic downturn. As a result, economic activity has lagged, and industrial countries have largely failed to fulfill their commitments to fund efforts to reduce hunger and improve food security. The number of hungry people spiked to more than 1 billion in 2009; the Millennium Development Goal of halving the proportion of hungry people by 2015 looked farther away than ever.